The Kerbal player's guide the easiest way to launch a space program - Manning, Jon; Nugent, Tim; Fenwick, Paul; Allan, Alasdair; Buttfield-Addison, Paris (O'Reilly Media, 2016)
Kerbal Space Program (KSP) is a critically acclaimed, bestselling space flight simulator game. It's making waves everywhere from mainstream media to the actual space flight industry, but it has a bit of a learning curve. In this book, five KSP nerds--including an astrophysicist--teach you everything you need to know to get a nation of tiny green people into space.
Includes index. - Online resource; title from PDF title page (EBSCO, viewed November 30, 2016)
Keywords: Kerbal (Game); Video games; Space flight -- Computer simulation; Flight simulation video games; Video Games; Jeux vidéo; Vol spatial; Simulation par ordinateur; Jeux vidéo de simulation de vol; video games; GAMES; Board; Space flight; Computer simulation